ACCELERATED DURABILITY ASSESSMENT OF TORSION BEAM REAR AXLE - TANG MingSong; WANG YanSong; ZHAO LiHui (Jixie qiangdu, 2017)
According to the understanding of the actual load effect on the rear axle,the invalid load interval of critical modulated signal can be decided to compile the multi-level program spectrum. The loading mode of bench test is simplified on the basis of recognization of the failure correlated load on the rear axle. Accordingly,the durability test of torsion beam rear axle is completed from the work above. The results show that the failure region of bench test is coincident with road test which can reach the accelerated assessment of durability,the acceleration factor is 5. 68.